2018
DOI: 10.3389/fpls.2018.01490
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Mediated Effects of Water Deficit on the Performance of Tetranychus evansi on Tomato Drought-Adapted Accessions

Abstract: Climate change is expected to increase drought periods and the performance and dispersal of some invasive species such as Tetranychus evansi, which has been reported to take advantage of the nutritional changes induced by water-shortage on the tomato cultivar Moneymaker (MM). We have examined the implications for mite’s biology of four accessions of the drought-adapted tomatoes, “Tomàtiga de Ramellet” (TR), under moderate drought stress. Mite performance was enhanced by drought in two accessions (TR61 and TR15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…In this regard, consumers appreciate that the skin, which is thick and hard, remains completely free of pericarp after spreading, which is uncommon in diverse Iberian Peninsula LSL landraces, and especially in commercialized 'de Ramellet'-like F 1 hybrids. Some landraces have proven to be tolerant to pests (Ximénez-Embún et al, 2018).…”
Section: Diversity and Distribution Of The Mediterranean Lsl Landracesmentioning
confidence: 99%
“…In this regard, consumers appreciate that the skin, which is thick and hard, remains completely free of pericarp after spreading, which is uncommon in diverse Iberian Peninsula LSL landraces, and especially in commercialized 'de Ramellet'-like F 1 hybrids. Some landraces have proven to be tolerant to pests (Ximénez-Embún et al, 2018).…”
Section: Diversity and Distribution Of The Mediterranean Lsl Landracesmentioning
confidence: 99%
“…However, this interaction has been shown to be more complex since it also depends on the plant species, the intensity and duration of the drought stress and the arthropod feeding mechanism [ 30 , 31 ]. Previous results coming from the analysis of the interaction between T. urticae or T. evansi and moderate water stress conditions in tomato plants (cv Moneymaker) showed the increase of both spider mite populations, thus confirming the modification of the plant–spider mite interaction under water stress conditions [ 21 , 32 , 33 ]. Moreover, the characterization of the T. evansi attack to traditional drought-tolerant tomato varieties has shown that adaptation of tomato plants to moderate drought modifies physiological plant responses to tomato red spider mite associated with an increase of tomato ABA levels [ 21 ].…”
Section: Introductionmentioning
confidence: 57%
“…Previous results coming from the analysis of the interaction between T. urticae or T. evansi and moderate water stress conditions in tomato plants (cv Moneymaker) showed the increase of both spider mite populations, thus confirming the modification of the plant–spider mite interaction under water stress conditions [ 21 , 32 , 33 ]. Moreover, the characterization of the T. evansi attack to traditional drought-tolerant tomato varieties has shown that adaptation of tomato plants to moderate drought modifies physiological plant responses to tomato red spider mite associated with an increase of tomato ABA levels [ 21 ]. All these previous results indicate that plant response mechanisms boosting T. evansi growth under drought stress conditions and those by which it supresses plant defences might be independent, and that ABA is involved in the fine-tune of spider mite-mediated plant defences [ 21 , 32 ].…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations